Long-Term Outcomes and Prognosticators of Pediatric Primary Dilated Cardiomyopathy in an Asian Cohort - Po-Yuan Wang; Po-Yuan Wang; Wei-Chieh Tseng; Chun-Min Fu; Mei-Hwan Wu; Jou-Kou Wang; Yih-Sharng Chen; Nai-Kuan Chou; Shoei-Shen Wang; Shuenn-Nan Chiu; Ming-Tai Lin; Chun-Wei Lu; et al. (Frontiers in Pediatrics, 2021)
Background: Dilated cardiomyopathy (DCM) is the most common childhood cardiomyopathy. The epidemiological profiles and prognosticators of clinical outcomes in Asian populations are not well elucidated.Methods: Data of 104 children aged <18 years with a diagnosis of primary DCM from January 1990 to December 2019 in our institutional database were retrospectively investigated. Relevant demographic, echocardiographic, and clinical variables were recorded for analysis. A P <0.05 was considered statistically significant.Results: The median age at diagnosis was 1.4 years (interquartile range = 0.3–9.1 years), and 52.9% were males. During a median follow-up duration of 4.8 years, 48 patients (46.2%) were placed on the transplantation waitlist, and 52.1% of them eventually received heart transplants. An exceptionally high overall waitlist mortality rate was noted (27.1%), which was even higher (43.5%) if the diagnostic age was <3 years. The 1-, 5-, and 10-year transplant-free were 61.1, 48.0, and 42.8%. Age at diagnosis >3 years and severe mitral regurgitation at initial diagnosis were independent risk factors for death or transplantation (hazard ratios = 2.93 and 3.31, respectively; for both, P <0.001). In total, 11 patients (10.6%) experienced ventricular function recovery after a median follow-up of 2.5 (interquartile range = 1.65–5) years. Younger age at diagnosis was associated a higher probability of ventricular function recovery.Conclusions: Despite donor shortage for heart transplantation and subsequently high waitlist mortality, our data from an Asian cohort indicated that transplant-free long-term survival was comparable with that noted in reports from Western populations. Although younger patients had exceptionally higher waitlist mortality, lower diagnostic age was associated with better long-term survival and higher likelihood of ventricular function recovery.